Bystander dalam Siklus Perundungan dan Implikasinya Terhadap Layanan Bimbingan dan Konseling - Anisa Rahmadani (Program Studi Bimbingan dan Konseling Universitas Muhammadiyah Tasikmalaya, 2020)
Bullying is a significant topict and is never used up to be discusses and become a global concern. Research showed that bullying interventions have not been fully effective and do not involve the role of bystander in bullying cycle. In fact, bystander acts as a powerful moderators of behavior. Bystander potential must be counted in intervention. This literature research aims to investigate the nature of bystander in bullying cycle and its implication for guidance and counseling